Translating Psychedelic Therapies From Clinical Trials to Community Clinics: Building Bridges and Addressing Potential Challenges Ahead - Williams, Martin L.; Korevaar, Diana; Harvey, Renee; Fitzgerald, Paul B.; Liknaitzky, Paul; O'Carroll, Sean; Puspanathan, Prashanth; Ross, Margaret; Strauss, Nigel; Bennett-Levy, James (Frontiers in Psychiatry, 2021)
Research to explore the potential of psychedelic-assisted therapies to treat a range of mental illnesses is flourishing, after the problematic sociopolitical history of psychedelics led to the global shutdown of clinical research for almost forty years. Encouraged by positive results, clinicians and patients hope that further interruptions to research will be avoided, and that the early promise of these therapies might be fulfilled. Researchers are currently focused on late-phase clinical trials, with relatively little consideration given to longer-term goals such as translation to community practice. Looking to identify and avoid potential pitfalls on the path to community clinics, a group of Australian clinicians and researchers met for a series of workshops to discuss possible obstacles. Five broad categories of challenge were identified. Analysis led to some strategies, including public sector support of research and training to establish best practice and optimize translation, and funding to address issues of equitable access to treatment. Above all, strategic planning and professional cohesion are likely to be crucial for success. Accordingly, our key recommendation is the establishment of a multidisciplinary advisory body, broadly endorsed and representing all major stakeholders, to guide policy and implementation of psychedelic-assisted therapies in Australia. Although these challenges and strategies are framed within the Australian context, we sense that they may generalize to other parts of the world. Wherever they apply, we believe that anticipation of potential difficulties, and creative responses to address them, will be important to avoid roadblocks in the future and keep the “psychedelic renaissance” on track.